(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2017)
The knowledge arises from processes that relate experiences and information that is acquired through methodological and daily information systems, which impacts on creative ways of interpreting realities through cognitive processes, which involve a change in the way of being of people to be in society, socioformation provides methods that involve using students’ experiences, modifying the dynamics of learning, achieving an understanding of a more diffuse reality, which globalization is the main protagonist; the event of the II International Congress of Evaluation of Performance Values 2017, held on October 6 and 7, in a virtual way, as an objective, research and dissemination proposals were promoted in the educational field, the experts propose to develop an evaluation from a socioformative concept, which impacts on the design of instruments, validation, evaluation, application of tests, generate systemic processes on the evaluation of learning; researchers from educational institutions and service providers promote methodologies that respond to these changes and impact the teacher and student for real educational efficiency; plans, programs, systems, theory, praxis, being, knowing how to live together are general elements that should be integrated into any educational process, presented in class plans that are promoters of sustainable training, especially that responds to the demands of the environment personnel, in the area of local population, as well as with an assimilation of response to the global process.